Building Sustainable School Governance through Participatory Decision-Making and Ethical Management - Pierre Marcello Lopulalan (PT FORMOSA CENDEKIA GLOBAL, 2026)
Sustainable school governance has become a key issue in modern educational management due to growing demands for transparency, accountability, and stakeholder involvement. This study examines the role of participatory decision-making and ethical management in strengthening sustainable school governance. Using a mixed-methods explanatory design, the research was conducted at a public senior high school in Serang City, Banten. Quantitative data were collected from a survey of 60 respondents, while qualitative data were obtained through in-depth interviews with eight key informants and institutional document analysis. Quantitative analysis employed structural regression techniques, and qualitative data were thematically coded. The results show that participatory decision-making significantly enhances trust, transparency, and accountability, while ethical management reinforces leadership integrity and consistency in governance practices. Together, these factors synergistically support more adaptive, inclusive, and sustainable school governance. The study highlights the importance of integrating stakeholder participation and managerial ethics as a foundation for strengthening educational governance and contributes both theoretically and practically to governance models in local and regional contexts.